2017
DOI: 10.1038/ajg.2016.610
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach to Pancreas Cancer in 2016: A Review

Abstract: In this article, we review our multidisciplinary approach for patients with pancreatic cancer. Specifically, we review the epidemiology, diagnosis and staging, biliary drainage techniques, selection of patients for surgery, chemotherapy, radiation therapy, and discuss other palliative interventions. The areas of active research investigation and where our knowledge is limited are emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
86
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 161 publications
0
86
0
6
Order By: Relevance
“…Surgical resection and chemotherapy were considered to be the main treatment options for pancreatic cancer [2]. Unfortunately, even with the advancement in medicine, pancreatic cancer is still resistant to current treatment regimens [3].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection and chemotherapy were considered to be the main treatment options for pancreatic cancer [2]. Unfortunately, even with the advancement in medicine, pancreatic cancer is still resistant to current treatment regimens [3].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this study included patients who are older and more often female than the general pancreatic cancer population, so the results may not be generalizable. 1 Although recent prospective studies have shown high rates of postoperative complications in patients who underwent ERCP before surgery for pancreatic cancer, ERCP still is used frequently in this situation. In this large population-based analysis, we did not find an effect of preoperative ERCP on mortality after controlling for confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…S urgical resection is the only option for cure for patients newly diagnosed with pancreatic cancer located in the head of the pancreas. 1,2 However, surgery may be delayed by the need for definitive diagnosis, symptoms of biliary obstruction, or the need for neoadjuvant treatment. [2][3][4] Endoscopic retrograde cholangiopancreatography (ERCP) may be used to relieve symptoms of jaundice as well as to normalize bilirubin levels so neoadjuvant chemotherapy can be administered before surgical resection.…”
mentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer-related death and tumor resection is still the only potentially curative treatment (1). However, because PDAC patients are prone to develop systemic metastasis early in the course of the disease, the risk of tumor recurrence remains extraordinarily high with a 5-year survival rate of 10% after surgery alone and up to 25% with adjuvant chemotherapy, preferably gemcitabine (2).…”
Section: Introductionmentioning
confidence: 99%